Decarboxylative Alkynylation. (1st August 2017) - Smith, Joel M.; Qin, Tian; Merchant, Rohan R.; Edwards, Jacob T.; Malins, Lara R.; Liu, Zhiqing; Che, Guanda; Shen, Zichao; Shaw, Scott A.; Eastgate, Martin D.; Baran, Phil S.
Abstract: The development of a new decarboxylative cross‐coupling method that affords terminal and substituted alkynes from various carboxylic acids is described using both nickel‐ and iron‐based catalysts. The use of N‐hydroxytetrachlorophthalimide (TCNHPI) esters is crucial to the success of the transformation, and the reaction is amenable to in situ carboxylic acid activation. Additionally, an inexpensive, commercially available alkyne source is employed in this formal homologation process that serves as a surrogate for other well‐established alkyne syntheses. The reaction is operationally simple and broad in scope while providing succinct and scalable avenues to previously reported synthetic intermediates.